The big easy - Quaid, Dennis; Barkin, Ellen; Beatty, Ned; McBride, Jim (HBO Video, 1987)
A slick New Orleans detective uncovers a heroin-based mob war while romancing an uptight assistant DA who in turn is investigating his corrupt department.